In Vitro Antioxidant Potential of Aqueous and Organic Extracts of Clematis connata - Zahid Qureshi, Muhammad; Ali Rana, Faraz; Kausar, Rukhsana; Shahwar, Durre; Asam Raza, Muhammad (Asian Journal of Chemistry, 2011)
The aerial parts of Clematis connata were extracted in methanol-water (90:10) and partitioned with n-hexane, chloroform, ethyl acetate and n-butanol successively using partition chromatography. Total phenolic contents of all extracts were determined, using Folin-Ciocalteu reagent and ranged between 15.9 ± 0.8 to 265.7 ± 1.4. The antioxidant potential of extracts was evaluated viz.; DPPH, FRAP, ABTS and total antioxidant models. Ethyl acetate extract showed highest activity in DPPH (93 ± 1.6 %, IC50 104 ± 1.5 μg) FRAP (6.3 ± 0.3), ABTS (0.405) and total antioxidant (1.098 ± 0.05). A strong correlations observed between total phenols, total antioxidant activity, DPPH and FRAP with R2 values ranged from 0.7881-0.8827.